2020
DOI: 10.31235/osf.io/rd7xf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Long Run Evolution of Absolute Intergenerational Mobility

Abstract: This paper combines cross-sectional and longitudinal income data to present the evolution of absolute intergenerational income mobility in ten developed economies in the 20th century. Absolute mobility decreased during the second half of the 20th century in all these countries. Increasing income inequality and decreasing growth rates have contributed to the decrease. Yet, growth is the dominant contributor in most countries. We show that detailed panel data are unnecessary for estimating absolute mobility over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 6 publications
3
41
1
Order By: Relevance
“…It eliminates the need for detailed panel data or synthetic matching approaches. Unlike absolute intergenerational mobility, which is found as insensitive to the copula (Berman, 2018), we find that absolute mobility is very sensitive to changes in the copula when there is very little relative mobility. Our methodology also allows overcoming limitations related to the nature of the available data.…”
Section: Introductioncontrasting
confidence: 76%
See 1 more Smart Citation
“…It eliminates the need for detailed panel data or synthetic matching approaches. Unlike absolute intergenerational mobility, which is found as insensitive to the copula (Berman, 2018), we find that absolute mobility is very sensitive to changes in the copula when there is very little relative mobility. Our methodology also allows overcoming limitations related to the nature of the available data.…”
Section: Introductioncontrasting
confidence: 76%
“…They found that it has fallen from around 90% for children born in 1940 to 50% for children born in the 1980s. Berman (2018) showed a similar trend in other countries, also establishing the robustness of the estimation methodology of absolute mobility.…”
Section: Introductionsupporting
confidence: 67%
“…Some participants we considered to have stationary high SES might have experienced lower SES between these time points. Data showing that social mobility is limited suggest that participants who reported high childhood and high current SES are more likely to have experienced high SES between these time points rather than a drop in their SES (Berman, 2019; Chetty et al, 2017). Moreover, if the standing of participants who we considered to be stationary high SES actually changed during their lifetime, they should still be more stationary than those who reported low SES during their childhood, currently, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of intergenerational social mobility are declining in many countries (Berman, 2019; Chetty et al, 2017), such that those born into high socioeconomic status (SES) households are increasingly likely to maintain that standing in adulthood, whereas those born into less privileged circumstances are becoming less likely to achieve high SES. It is, therefore, important to understand the psychological effects of entrenched socioeconomic privilege.…”
mentioning
confidence: 99%
“…Based on far more birth cohorts and much longer observational windows of income than previous studies, we can investigate how genetic and environmental factors change in relation to lifetime income throughout rapid societal changes in gender equality. Norway makes a particularly compelling case as it's one of the most gender-equal countries in the world (UNDP 2018), as well as being characterized by comparatively low income inequality (Modalsli, Aaberge, and Atkinson 2017) and high social mobility (Berman 2018). Our findings based on genetically sensitive variance decompositions show that as the gender income gap decreases, the heritability of lifetime income increases.…”
Section: Introductionmentioning
confidence: 99%